2010
DOI: 10.2136/sssaj2009.0437
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bio‐Organic Fertilizer Significantly Affected Fungal Diversity of Soils

Abstract: Cotton verticillium wilt (Verticillium dahliae Kleb.) is a very destructive disease. In this study, we evaluated a Bacillus subtilis enhanced bio-organic fertilizer (BOF) for control of the disease and for its eff ect on rhizosphere microbiota. Greenhouse pot experiments were conducted during three cotton (Gossypium hirsutum L.) growing seasons with serial treatments of BOF or unenhanced organic fertilizer (OF). Consistent control of cotton verticillium wilt was obtained in the three trials. Th e complete BOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 71 publications
(68 reference statements)
6
34
0
Order By: Relevance
“…In a comparative study on different organic amendments, Shen et al (2013) found that bio-organic fertilizer was the most effective in improving soil microbial communities, suppressing Fusarium wilt disease in banana, and enhancing yield and quality of banana. Luo et al (2010) also showed that application of bio-organic fertilizer formulated with Bacillus subtilis biological control agent significantly improved fungal population composition in rhizosphere soils and effectively controlled cotton verticillium wilt. In our present experiments, bio-organic fertilizer showed significant roles in enhancing Chuju yield and quality and suppressing Fusarium population, but it is necessary to further examine bio-organic fertilizer impact on microbial community dynamics and its duration.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In a comparative study on different organic amendments, Shen et al (2013) found that bio-organic fertilizer was the most effective in improving soil microbial communities, suppressing Fusarium wilt disease in banana, and enhancing yield and quality of banana. Luo et al (2010) also showed that application of bio-organic fertilizer formulated with Bacillus subtilis biological control agent significantly improved fungal population composition in rhizosphere soils and effectively controlled cotton verticillium wilt. In our present experiments, bio-organic fertilizer showed significant roles in enhancing Chuju yield and quality and suppressing Fusarium population, but it is necessary to further examine bio-organic fertilizer impact on microbial community dynamics and its duration.…”
Section: Discussionmentioning
confidence: 92%
“…Bio-organic fertilizer is an organic amendment inoculated with living beneficial micro-organisms. It has showed better roles in improving plant growth and suppressing disease than common organic amendments have (Ahmad et al, 2008;Luo et al, 2010;Ding et al, 2013). In a comparative study on different organic amendments, Shen et al (2013) found that bio-organic fertilizer was the most effective in improving soil microbial communities, suppressing Fusarium wilt disease in banana, and enhancing yield and quality of banana.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations